Towards a management database to improve the sustainability of cattle production and its contribution to food security : a case of emerging beef farmers in Limpopo Province, South Africa - Mapiye, Obvious (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.